MPO: A Menace to Fundamental Rights - Unveiling the Abuses (Journal of Social Sciences Review, 2023)
This research article delves into the enduring challenges faced by our country in ensuring the preservation of constitutional liberties, even long after the end of the British colonial era. Examining the notion of "might is right" prevalent in our society, we highlight the existing disparity between the Constitution's perceived strength and its practical application. By scrutinizing the principle of strict construction of laws, we explore how it poses significant threats to citizens' liberties. While stringent interpretation may appear necessary for national security and governance, it often leads to an unjust infringement upon individual rights. This study emphasizes the importance of imposing limitations on government requirements to safeguard against arbitrary deprivation of liberty. By advocating for due care, caution, and attention in the decision-making process, we aim to foster a more balanced approach that respects citizens' fundamental rights while ensuring effective governance. Through an in-depth analysis of relevant legal precedents, we propose alternative strategies and reforms that can mitigate the existing shortcomings in upholding constitutional liberties, promoting a society where justice and freedom prevail.
Keywords: MPO; Constitutional Liberties; Strict Construction; Individual Rights; Government Requirements; Deprivation of Liberty